Integrating Nutrigenomics And Traditional Wisdom: A Study Of Dietary Ethics In Islamic Hadith And Kitab Al-rahmah Fi Al-tibb Wa Al-hikmah - Nurulwahidah Mohd Fauzi; Robiatul Adawiyah Mohd @ Amat; Norzulaili Mohd Ghazali (USIM Press, 2024)
Ulum Islamiyyah, Volume 36 Issue 03 Page (79–97)